KAJIAN KESESUAIAN MANAJEMEN BENCANA TERHADAP KOMPONEN MANAJEMEN BENCANA PADA KAWASAN RAWAN BENCANA TANAH LONGSOR TINGGI DI KABUPATEN KARANGANYAR - Oktavian Cendhy Bunga Pratama; Murtanti Jani Rahayu; Rufia Andisetyana Putri (ARSITEKTURA, 2017)
Abstract : Karanganyer regency’s government has set the area – the area that potentially catastrophic landslide in Karanganyaer regency a spatial plan of karanganyar regency in 2012 -2031. The area prone to high landslide disaster has greater risk in the event of catastrophic landslide, so that the disaster management has more pay attention in the area prone to high landslide disaster. The problem in this research in how the suitability of disaster management in areas prone to landslides high Karanganyar regency towards disaster management component. The purposes of this research is to know the suitability of disaster management in areas prone to landslides high Karanganyar towards disaster management component. This research use deductive qualitative approaches. The results of this study shows in the area prone to high landslide disaster of Karanganyar regency has reached compliance. Area prone to high landslide disaster not have “early warning system” and warning light yet, but have applied conventional voice signal. Has been designated evacuation meeting point even though the capacity has not enough. Evacuation lanes using existing road network and currently there are not evacuation lanes and evacuation fringes yet. The relocation has been implemented on the residents who occurred landslide and homeless lived.Keyword: disaster management, disaster-prone area of landslide